The The Effect of Problem Based Learning Integrated with Deep Learning on Students’ Mathematical Reasoning Ability - Zakiya Amalia Hartanto Putri; Hepsi Nindiasari (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to determine the effect of the Problem Based Learning model integrated with Deep Learning on junior high school students’ mathematical reasoning ability, as well as the level of improvement after the learning intervention. This research employed a quantitative approach using a quasi-experimental One-Group Pretest–Posttest design. The sample consisted of one class of junior high school students who received problem-based learning with a deep learning approach over four sessions. The research instrument was a mathematical reasoning test administered before and after the intervention. Data were analyzed using descriptive statistics, normality testing, paired sample t-test, and N-Gain analysis. The results show that the Problem Based Learning model with Deep Learning has a significant effect on students’ mathematical reasoning ability, indicated by a significance value of p < 0.05. Furthermore, the N-Gain analysis revealed a moderate level of improvement. Thus, the Problem Based Learning model integrated with Deep Learning is effective in enhancing students’ mathematical reasoning ability.